Upaya Meningkatkan Kemampuan Berbicara (Speaking) Peserta Didik Pada Materi Expressing Opinion and Thought Melalui Media Video Di Kelas Xi TBSM 1 SMKN 4 Kota Serang Tahun Ajaran 2021/2022 - Kurniasari, Fitriana (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2022)
The purpose of this study is to investigate how class XI TBSM 1 students in Serang City acquire speaking skills in English subjects through the use of video media, and to determine whether the use of video media can improve their speaking skills. The research was conducted during October to November 2021 (Semester III of 2021/2022) and involved 15 students of class XI TBSM 1 at SMKN 4 Serang City. A qualitative approach, specifically participatory and collaborative research on classroom activities, was used. The researchers served as the primary data collection instrument, observing the learning activities, social phenomena, and psychological symptoms that occurred in the classroom. The data was analyzed by processing and reviewing the information obtained and supported by relevant theory and literature. The findings showed that the implementation of speaking skills through video media can improve the ability of class XI TBSM 1 students at SMKN 4 Serang City. The key factors for success included competent teachers, interesting materials, adequate media, and a conducive learning environment, as well as the students’ own abilities. The use of video media also made the material more engaging and easier to understand, leading to an increase in students’ conversational skills and their ability to express their opinions and thoughts. Furthermore, the use of video media was found to improve student learning outcomes, as evidenced by an increase in average grades, class completion rates, and individual student grades.